Extinction and recovery patterns of scleractinian corals at the Cretaceous-Tertiary boundary - Kießling, Wolfgang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2004)
The extinction and recovery of scleractinian corals at the Cretaceous-Tertiary (K-T) boundary was analyzed based on a global database of taxonomically revised late Campanian to Paleocene coral collections. In contrast to earlier statements, our results indicate that extinction rates of corals were only moderate in comparison to other marine invertebrates. We have calculated a 30% extinction rate for Maastrichtian coral genera occurring in more than one stratigraphic stage and more than one geographic region. Reverse rarefaction suggests that some 45% of all coral species became extinct. Photosymbiotic (zooxanthellate) corals were significantly more affected by the extinction than azooxanthellate corals; colonial forms were hit harder than solitary forms, and among colonial forms an elevated integration of corallites raised extinction risk. Abundance, as measured by the number of taxonomic occurrences, had apparently no influence on survivorship, but a wide geographic distribution significantly reduced extinction risk. As in bivalves and echinoids neither species richness within genera nor larval type had an effect on survivorship. An indistinct latitudinal gradient is visible in the extinction, but this is exclusively due to a higher proportion of extinction-resistant azooxanthellate corals in higher-latitude assemblages. No significant geographic hotspot could be recognized, neither in overall extinction rates nor in the extinction of endemic clades. More clades than previously recognized passed through the K-T boundary only to become extinct within the Danian. These failed survivors were apparently limited to regions outside the Americas. Recovery as defined by the proportional increase of newly evolved genera, was more rapid for zooxanthellate corals than previously assumed and less uniform geographically than the extinction. Although newly evolved Danian azooxanthellate genera were significantly more common than new zooxanthellate genera, the difference nearly disappeared by the late Paleocene suggesting a more rapid recovery of zooxanthellate corals in comparison to previous analyses. New Paleocene genera were apparently concentrated in low latitudes, suggesting that the tropics formed a source of evolutionary novelty in the recovery phase. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IGM.LP.extinc
Keywords: Corals; Cretaceous-Tertiary boundary; Evolution; Mass extinction; Reefs